A compact flexible filtering antenna for body area network. Issue 3 (29th November 2021) - Cui, Jingyu; Zhang, Anxue; Yan, Sen
Abstract: A compact flexible wearable filtering antenna for body area network application scenarios is presented in this letter. The module is composed of a simple rectangular patch antenna tightly integrated with a bandpass filter based on multilayered hairpin resonators. The antenna is designed and fabricated by flexible textiles, which plays the last order of the filter. The introduction of the filter structure on a small solid substrate is used to enhance the frequency selectivity and the impedance matching, which will not affect the flexibility of the whole module. A good agreement is obtained between the simulation and the measurement result. It shows that the filtering antenna achieve an operating band from 5.08 to 5.96 GHz with realized gain higher than 5 dBi, and the bandwidth is stable when the antenna is placed on human body with bending scenario.